MUNICIPAL SOLID WASTE MANAGEMENT: THE VISION OF POPULATION IN THE CITY OF FREDERICO WESTPHALEN - Kemerich, Pedro Daniel da Cunha; Rodrigues, Alexandre Couto; Ucker, Fernando Ernesto; Renz, Vanessa Deisi; Haas, Aline (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707436 The society involvement in environmental issues is of extreme necessity, where each individual is responsible for the production and disposal of their waste, thus establishing a link between citizenship and environmental education. Household waste are part of the villain that links the destruction of the environment and depletion of natural resources, in addition to numerous problems. This study aimed to identify ways to dispose of, knowledge about household waste separation methods and disposal of these materials, used by the population of the city of Frederico Westphalen - RS, as well as environmental damage and correct ways to reduce these impacts with new methods of conscious consumption. The study demonstrated that the higher the education level of the individual, the greater its environmental awareness.